First Year Nursing Students' Coping Strategies in Stressful Clinical Practice Situations - Iwona Bodys-Cupak; Anna Majda; Justyna Skowron; Joanna Zalewska-Puchała; Aneta Trzcińska (Journal of Education in Science, Environment and Health)
Performing the social service professions, to which a profession of nurse includes, is considered one of the most stress-inducing jobs. The reason behind this is deep emotional involvement in contact with patient followed by responsibility for human health and life. The time dedicated to gaining knowledge and practical skills constitutes both a potential stress source for the nursing students and provides them with the opportunity to learn how to cope with it. This study aims at assessing the level of stress in difficult situations, differentiating the methods of stress coping and difficult situations for the nursing studies in the course of practical training. 110 first-year students of intramural studies at the Nursing Faculty, State Higher Vocational School in Tarnów (southern Poland) were surveyed using the research tools include the author's survey questionnaire, Perceived Stress Scale, Inventory to Measure Coping Strategies with Stress. Differences between variables were verified using the chi-square (χ2) independence test and Mann - Whitney test. The adopted significance level was α=0.05. During the first practical training, the nursing students struggled with multiple difficult situation (and perceived moderate and high stress and their attempts to cope with stress were diversified. Increase in stress level was accompanied by higher frequency of stress copying strategies by avoidance behaviours (χ2=7.59; p=0.02). Students in difficult situations have more frequently applied coping strategies involving focusing on the issue of concern rather than emotion-based strategies. One should develop active methods of coping with stress and difficult situations with the nursing students, including in particular these manifesting helplessness and avoidance behaviours.